(untitled) (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
Studying the performing art of wayang golek in the late 1970s required learning how to learn a complex art in a local language from village practitioners whose practice did not correspond to the model expounded by the local academic. Language, music, culture, dance, spiritual dimensions, and complex stories needed to be absorbed and became building blocks toward performing this rich art of the Sundanese dalang of West Java. Keywords: Wayang Golek. Sundanese rod puppetry. Dalang.